Far-right movements in the Western world: how media exposure relates to normative beliefs and attitudes toward the far-right - Selvanathan, Hema Preya; Leidner, Bernhard; Syropoulos, Stylianos; Louis, Winnifred; Adelman, Levi; Baka, Aphrodite; Bauer, Christina; Blikmans, Martijn; Becker, Maja; Beran, Eszter; Bilewicz, Michał; Chekroun, Peggy; et al. (Group processes & intergroup relations, 2025)
Considering the rise of far-right groups in Western countries, we examined whether exposure to media coverage on the far-right is associated with attitudes toward it, using surveys in 15 Western democratic countries (total N = 2,576). We hypothesized that greater media exposure to the far-right will be associated with greater perceived prevalence and acceptability of it, which will in turn be associated with divergent attitudes. On the one hand, greater perceived prevalence may be associated with more unfavorable attitudes toward the far-right (a threat response). On the other hand, greater perceived acceptability may be associated with more favorable attitudes toward the far-right (a normalization response). Overall, there was more evidence for a threat response than a normalization response: media exposure was consistently related to greater perceived prevalence (but not acceptability) of the far-right. This research underscores the importance of studying the consequences of the rise of the far-right.